Opportunities and Challenges of Generative AI in Shaping the Future of Education in Thailand: A Narrative Review - Basel Abdulwahab; Suhairee Beungacha; Rungchatchadaporn Vehachart (Buletin Edukasi Indonesia, 2026)
This narrative review examines the emerging role of Generative Artificial Intelligence (GenAI) in shaping the future of education in Thailand. Drawing on scholarly literature published between 2020 and 2025, the review synthesizes current trends, empirical findings, and conceptual discussions related to the integration of GenAI in educational systems. The analysis highlights key opportunities offered by GenAI, including personalized and adaptive learning experiences, intelligent tutoring systems, automated feedback, and support for educational innovation aligned with national digital transformation agendas. At the same time, the review identifies significant challenges that may hinder effective adoption, such as digital inequality, data privacy and ethical concerns, limited institutional infrastructure, and varying levels of teacher readiness and digital competence. By critically discussing these opportunities and challenges, the review provides a balanced perspective on GenAI implementation in the Thai context. The study concludes by offering strategic recommendations for policymakers, educators, and researchers to promote responsible, inclusive, and sustainable use of GenAI in advancing the quality and equity of education in Thailand.